Dissolved Gas Analysis on POME-based Nanofluids - Sharifah Masniah, Wan Masra; Yanuar Zulardiansyah, Arief; E., Musa; N. I., Hashim; Nazreen, Junaidi; S., Umang; Siti Kudnie, Sahari; Asrani, Lit; Nur Sabrina, Suhaimi
This paper investigates the dissolved gas analysis (DGA) of aged palm oil methyl ester (POME)-based nanofluids. Thermal stress is applied to nanofluids with various concentrations of TiO2 and MWCNT nanoparticles. The experiments are conducted on a laboratory scale, with the POME-based nanofluids thermally aged at 130 oC in the absence of solid insulating materials. The study aims to compare the gases generated in both nanofluids. Four different diagnosis methods are employed: Rogers Ratio, IEC Gas Ratio, Duval Triangle, and Duval Pentagon. The experimental results reveal nearly identical gassing behaviors between the two nanofluids after thermal ageing. These findings contribute to expanding investigations into transformer fault diagnosis, particularly in cases where various natural ester oils, including POME-based nanofluids, are used in power transformer. This helps diversify the growing body of research on DGA for natural ester oils, which has largely focused on commercially dominant types.